Glecaprevir/pibrentasvir is safe and effective in hepatitis C patients with cirrhosis: Real‐world data from the German Hepatitis C‐Registry. (1st March 2021) - Wedemeyer, Heiner; Erren, Peter; Naumann, Uwe; Rieke, Ansgar; Stoehr, Albrecht; Zimmermann, Tim; Lohmann, Kristina; König, Bettina; Mauss, Stefan
Abstract: Glecaprevir/pibrentasvir is a pangenotypic direct‐acting antiviral regimen approved for treating chronic hepatitis C virus. Real‐world use of protease‐inhibitor–containing regimens requires further evaluation in patients with cirrhosis. We evaluated the real‐world safety and effectiveness of glecaprevir/pibrentasvir in patients with cirrhosis from the German Hepatitis C‐Registry who initiated treatment between 2 August 2017‐30 June 2019. Overall, 131 patients received on‐label treatment. No patient discontinued treatment due to adverse events. Four patients had serious adverse events; none were considered related to glecaprevir/pibrentasvir. Two patients had total bilirubin >5 × upper limit of normal (ULN) during treatment. Three patients had alanine aminotransferase and three patients had aspartate aminotransferase >3 × ULN. Rates of sustained virologic response were 100% (86/86) for 86 patients with available data. A total of 51 patients received off‐label treatment, of which 3 had a serious adverse event. Glecaprevir/pibrentasvir treatment was well‐tolerated and highly effective in patients with chronic hepatitis C and cirrhosis in real‐world practice.